Runoff Coefficient Analysis After Regional Development in Tambakbayan Watershed, Yogyakarta, Indonesia - Slamet Suprayogi; M Widyastuti; M Pramono Hadi; Nugroho Christanto; Tommy Andryan Tivianton; Gita Oktaviani Fadhilah; Laelina Rahmawati; Lintang Nur Fadlillah (Jurnal Ilmu Lingkungan)
The Tambakbayan Watershed has experienced changes in its land utilization. Based on land-use data from 2006 and 2017, built-up land was found to have encroached on vegetated areas and showed a substantial increase in area. Such conversion can alter and modify runoff coefficients, as a measure of watershed response. This research aimed to evaluate land-use change in the watershed from 2006 through 2017 and its effects on runoff coefficients. It used descriptive quantitative methods combining literature study and data calculation. The secondary data were obtained from digital land-use maps (RBI) in 2006 and 2017, SRTM images, soil types, and the drainage network of the watershed. Runoff coefficient analysis confirmed that the land-use change between 2006 and 2017 caused by regional development increased the runoff coefficients of the watershed observed.